Construction of 1D Ag-AgBr/AlOOH Plasmonic Photocatalyst for Degradation of Tetracycline Hydrochloride - Zhang, Siyang; Khan, Iltaf; Qin, Xiaohong; Qi, Kezhen; Liu, Ying; Bai, Shuchong (Frontiers in Chemistry, 2020)
In this work, the highly efficient and low-cost Ag-AgBr/AlOOH plasmonic photocatalyst is successfully prepared via a simple and mild wet-chemical process and used for degrading high concentration methylene blue (MB) and tetracycline hydrochloride (TCH). The optimized 6-Ag-AgBr/AlOOH sample has showed 79% decomposition of TCH in 2 hours, which is almost 2 times higher than that of bare AgBr (37%). For degrading MB, the photocatalytic activity of 6-Ag-AgBr/AlOOH (decomposing 84% in two hours) showed big enhancement as compared to bare AgBr (only 57%). The TEM, HRTEM, XRD, DRS and XPS characterization results confirm that Ag-AgBr is a composite catalyst formed by loading Ag nanoparticles on AgBr surfaces and then fruitfully loaded on to AlOOH. The possible mechanism proposed that •O2-, •OH radicals produced under sun light are the main active species for degrading MB and TCH. It is hoped that this work will open a new gateway to synthesis of highly efficient and low-cost Ag-AgBr/AlOOH plasmonic photocatalysts for degrading organic pollutants.